Iowa Birdline update, August 4, 1992 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1992)
Iowa Birdline updates for August 4, 1992. The highlights for the update include sightings of the continued presence of the juvenile Laughing Gull at Red Rock Reservoir and American Avocets at Saylorville Lake. Epson - sheet feed/flatbed